دراسة مقارنة لتقییم الأداء المصرفي بالاعتماد على مؤشرات السیولة والربحیة للمصارف المدرجة في بورصة فلسطین للمدة 2010- 2017 - Nouaf Abed, Mohammed (Finance and Business Economies Review, 2018)
The study aims at comparing the performance of banks listed on the Palestine Stock Exchange in the period 2010-2017 based on the averages of liquidity and profitability indicators, using the descriptive approach and the analytical method. The results showed instability in the Palestinian economic environment, which affected the results of performance of liquidity and profitability, where the highest indicators of liquidity in the Arab Islamic Bank (55.667%), while the profitability indicators the best results were in the Bank of Palestine. This confirms that Islamic banks maintain cash liquidity more than commercial banks because they are unable to provide liquidity at any time.The study recommends the adoption of indicators of liquidity and profitability in risk management and analysis by banks because of their importance in deviating degrees and levels of safety to avoid risk